Noninvasive and Safe Cell Viability Assay for Breast Cancer MCF-7 Cells Using Natural Food Pigment - Kyohei Yamashita; Ryoma Tagawa; Yoshikazu Higami; Eiji Tokunaga (Biology, 2020)
A dye exclusion test (DET) was performed to determine the viability of human breast cancer cells MCF-7, using natural food pigments as compared with trypan blue (TB), a typical synthetic dye for DET known to exhibit teratogenicity and cytotoxicity. We demonstrated that Monascus pigment (MP) is noninvasive to living cells and can effectively stain only dead cells. This study is the first verification of the applicability of MP to cancer cells. The appropriate MP concentration was 0.4% (0.02% as the concentration of pure MP) and all the dead cells were stained within 10 min. We found that the cell proliferation or the reduced nicotinamide adenine dinucleotide (NADH) activity of living cells was maintained over 48 h. Although 0.1% TB did not show an increase in dead cells, a marked decrease in NADH activity was confirmed. In addition, even when MP coexisted with cisplatin, staining of dead cells was maintained for 47 h, indicating stability to drugs (reagents). The cost of MP is estimated to be about 1/10 of TB. The fact that MP can be used as a cell viability determination reagent for Euglena and Paramecium, as shown in preceding papers, and also for MCF-7, as shown in this paper, indicates the possibility of application in more cells of different species.